2020
DOI: 10.3390/ijerph17124553
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Occupational Asthma

Abstract: Occupational asthma (OA) represents one of the major public health problems due to its high prevalence, important social and economic burden. The aim of this review is to summarize current data about clinical phenotypes, biomarkers, diagnosis and management of OA, a subtype of work-related asthma. Most studies have identified two phenotypes of OA. One is sensitizer-induced asthma, occuring after a latency period and caused by hypersensitivity to high- or low-molecular weight agents. The other is irritant-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 102 publications
(208 reference statements)
1
23
1
7
Order By: Relevance
“…These results are consistent with those from Torén et al and Le gested that solvents were associated with adult-onset asthma [23 also consistent with a few studies on trichloroethylene and paints gested an association between these chemicals and asthma or respi ciations between inks, which contained acrylates, and adult-onset a reported [39]. Associations between formaldehyde, a known asthm comes were not entirely consistent in our analyses, in particular in formaldehyde is now classified as a human carcinogen by the Int Research on Cancer (IARC) [40], its use has probably declined sinc our knowledge, occupational exposures to gasoline, cellulosic thi have never been studied in relation to asthma or respiratory disea first to show significant associations between several specific solv 1.0 * Exposure to at least one solvent: gasoline, trichloroethylene, white spirit, cellulosic thinner, forma paints/varnishes or inks/dyes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results are consistent with those from Torén et al and Le gested that solvents were associated with adult-onset asthma [23 also consistent with a few studies on trichloroethylene and paints gested an association between these chemicals and asthma or respi ciations between inks, which contained acrylates, and adult-onset a reported [39]. Associations between formaldehyde, a known asthm comes were not entirely consistent in our analyses, in particular in formaldehyde is now classified as a human carcinogen by the Int Research on Cancer (IARC) [40], its use has probably declined sinc our knowledge, occupational exposures to gasoline, cellulosic thi have never been studied in relation to asthma or respiratory disea first to show significant associations between several specific solv 1.0 * Exposure to at least one solvent: gasoline, trichloroethylene, white spirit, cellulosic thinner, forma paints/varnishes or inks/dyes.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are also consistent with a few studies on trichloroethylene and paints [16,25,38], which suggested an association between these chemicals and asthma or respiratory diseases. Associations between inks, which contained acrylates, and adult-onset asthma have also been reported [39]. Associations between formaldehyde, a known asthmagen, and asthma outcomes were not entirely consistent in our analyses, in particular in women.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Ni IgE-mediated hypersensitivity occurs most commonly as occupational hazards ( 24 ), where the prolonged exposures elicited Ni-interacting IgEs ( 25 ) through possible “non-antigenic” mechanisms ( 26 ) that arise from the expansion of existing IgEs (capable of additionally binding Ni) producing B-cells. We hypothesize the Ni-only specific IgEs to be extremely rare given the chemical nature of Ni, but rather that the unintended non-specific binding to Ni during antibody repertoire generation to other antigens occurred and were gradually selected for and expanded.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively young study population, chronic health problems can be in the preclinical phase and remain undiagnosed for long, manifesting only in old age when a causal relationship is difficult to establish. Dry cough and numbness or heaviness in the arms or legs could be associated with work in closed spaces of transportation and storage, representing respiratory irritation and peripheral neurotoxic effects, which are symptoms potentially induced by chemical exposures to fumigants and various solvents [ 28 , 29 , 30 ]. Although no significant correlation was found, trembling of hands, muscle cramps, slurred speech, and unpleasant taste in the mouth were more frequent among warehouse workers.…”
Section: Discussionmentioning
confidence: 99%